DANA DESA DAN UPAYA PENGENTASAN KEMISKINAN: STUDI KASUS JAWA TENGAH - Kuncoro, Trian Gigih; Arif, Muhammad; Primadani, Yulistya; Kurniawan, Wawan (Universitas Gunadarma, 2024)
This study focuses on poverty, an issue that affects every country, including developing ones like Indonesia. The primary objective is to investigate the impact of village funds (dana desa) on poverty in Central Java. Regional economic growth (PDRB) and the success of human development (IPM) are included in the research to provide a more balanced assessment. The research employs a data panel analysis with data from 29 districts over five periods (2016-2020). The findings reveal that poverty is influenced by village funds, showing a negative relationship. PDRB has a positive association with poverty, while IPM does not affect poverty levels. This study enhances our understanding of the connections between poverty, village funds, PDRB, and IPM at the provincial level. The implications of this research underscore the need for more precise policies in allocating village funds and a stronger focus on regional economic growth to alleviate poverty.